Pengaruh Pengalaman Kerja, Independensi, Integritas, Kompetensi Dan Etika Auditor Kualitas Audit - Muslim, Muslim; Nurwanah, Andi; Sari, Ratna; Arsyad, Muhammad (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2020)
The purpose of this study is to assess and evaluate the influence of work experience, autonomy, honesty, competence and audit ethics on the audit quality of the public accounting firm in Makassar city. This method of analysis used in the study is quantitative with primary data sources, which are data collected by administering questionnaires directly without intermediaries. Multiple linear regression analysis was used using the t-test to prove and evaluate this. There were 48 respondents to the number of samples in this report. The validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient determination test, t-test, and f test were used for data analysis. The conclusion of this analysis is that there is a positive and important influence of work experience on the consistency of audits. Freedom has a positive and powerful influence on the consistency of audits. Integrity has a positive and meaningful influence on the consistency of audits. Competence has a positive and important effect on the quality of the audit, and Auditor Ethics has a positive and important impact on the quality of the audit.